Mathematical Model of Community Participation Levels in Elections in Medan City - Chindy Aulia Putri; Rina Widyasari (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Political participation is one of the benchmarks of a country's democracy. This can be seen from their involvement in elections. Every general election must have a white group called abstainers who usually consciously do not using their voting rights which may influence individuals not to use their voting rights in general elections. Medan City is the city with the second highest number of abstainers in North Sumatra Province at 33.33%. This study will model the level of public participation in elections in Medan City by comparing the level of public participation in the 2019 and 2024 presidential elections. From the model, two equilibrium points are obtained, namely abstainer and abstainer-free equilibrium points, basic reproduction number and stability analysis of the equilibrium point. The simulation results for 2019 and 2024 showed that for , the abstainer population increases so that the abstainer equilibrium point is asymptotically stable. Then for , the abstainer population will gradually disappear